2011
DOI: 10.1007/s12070-011-0165-2
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxydase Expression in The Pathogenesis of Nasal Polyps

Abstract: Nasal polyps are benign mucosal protrusions that expand into the nasal cavity. There are no any etiological factors that may explain the pathogenesis of nasal polyps but currently inflammation continues to be the major factor. As a result of inflammation, neutrophils become activated and migrate to the inflammatory area and form their bactericidal effects by producing free oxygen radicals. The objective of our study is to investigate the expression of myeloperoxydase enzyme, which is usually an indicator of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…), and common sea-buckthorn (Hippophae rhamnoides). There were also daphne (Laurus nobilis) and narrow-leafed ash (Fraxinus angustifolia) trees in the study area (Sarısoy et al, 2007). In this study plot, human activities were very limited.…”
mentioning
confidence: 88%
“…), and common sea-buckthorn (Hippophae rhamnoides). There were also daphne (Laurus nobilis) and narrow-leafed ash (Fraxinus angustifolia) trees in the study area (Sarısoy et al, 2007). In this study plot, human activities were very limited.…”
mentioning
confidence: 88%
“…Nasal polyposis (NP) is a chronic inflammatory disease of the mucosa lining the nasal cavities and paranasal sinuses. 1,2 Its prevalence is 1% to4% in the general population, and it leads to complications such as nasal obstruction and rhinorrhea. 3,4 Although it is a well-known and easily diagnosed pathologic condition, its etiopathogenesis still requires discussion.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,8 Additionally, studies have shown that the immune system and oxidative stress play important roles in the formation and development of NP. 1,9,10 Many studies have been conducted in a search for treatments for NP, and many antioxidant and anti-inflammatory agents have been investigated as potential treatments for this disease.…”
Section: Introductionmentioning
confidence: 99%
“…There are no any etiological factors that may explain the pathogenesis of NPs but currently inflammation continues to be the major factor [2]. Many studies have pointed out that histopathologic abnormities of NP were closely related to the infiltration of inflammatory cells [3][4][5].…”
Section: Introductionmentioning
confidence: 99%